Heat Shock-Initiated Apoptosis Is Accelerated and Removal of Damaged Cells Is Delayed in the Testis of Clusterin/ApoJ Knock-Out Mice1 - Robert W. Bailey; Bruce J. Aronow; Judith A.K. Harmony; Michael D. Griswold (2002)
The secretion and localization of clusterin in the testis has led to the hypothesis that clusterin plays a role in spermatogenesis. Furthermore, the association of clusterin with apoptosis, cellular injury, disease, and regression of nongonadal tissues has led to the hypothesis that clusterin acts to protect cells from apoptosis or may be involved in tissue remodeling. To investigate the role of clusterin in the testis, we analyzed clusterin knock-out (cluKO) mice to determine the impact of the absence of clusterin on spermatogenesis. Furthermore, we investigated the cellular response to injury caused by methoxyacetic acid (MAA) toxicity and mild heat exposure in the cluKO mice to determine the extent to which clusterin protects against apoptosis or participates in tissue remodeling. We found that cluKO mice were fertile and had essentially normal spermatogenesis with the exception of some incomplete spermiation after stage VIII. No differences in testicular morphology or the incidence of apoptosis in the testis were seen between the cluKO and clusterin wild-type (cluWT) mice after MAA treatment. In contrast, apoptosis was delayed in the cluWT mice compared with the cluKO mice after heat exposure, suggesting that clusterin does have a slight protective effect against apoptosis under some conditions. Also, a dramatic loss of germ cells after heat stress occurred earlier in the cluWT testes than in the cluKO testes. Clusterin is clearly acting in a dual role in that cells can be protected from damage and dead cells can be more easily removed after some types of cellular damage but not after others.